Of being doctors and mercenaries - Abd Razak, Dzulkifli (2005)
THIS is the time of the year when tensions among youth and their families are high. It is the time of the year when careers are being decided upon, which in turn depends on which course that must be applied for depending on one's interest. This is no easy task because there are now scores of institutions of higher learning in the country offering thousands of courses. Some are rather new and less known and, therefore, remain unpopular. To some groups, however, no matter how many courses are available, they have made up their minds. Normally, they are attracted to the professional courses, notably medicine, which makes admission very competitive and invariably leading 10 controversy.